Combined Localization Method for Multimodal Wheel-Track Robots in Sheltered Space - Jiazhen Lin; Zhong Su; Hui Zhao; Yuxin Zhao; Xinkai Wang; Hao Zhou (IEEE Access)
In response to the localization challenges posed by multi-modal motion mode transitions during the locomotion of tracked-wheel robots in sheltered spaces, this paper presents a combination localization method based on Inertial Navigation System/Odometry (INS/OD). Leveraging the unique locomotion structure of tracked-wheel robots, a multi-modal odometry motion model and non-holonomic constrained (NHC) velocity model are established. A closed-loop extended Kalman filter is employed to construct the combination localization model, facilitating real-time computation and correction of the robot’s heading angle using the odometry motion model, effectively mitigating system errors and preventing heading divergence. The wheeled-track robot was subjected to outdoor and underground tunnel real-world localization tests. The results demonstrate that the proposed combined localization method achieved an absolute positioning accuracy of the wheeled-track robot within 0.3578 meters in outdoor experiments. This accounts for only 0.31% of the total distance traveled in the outdoor experiments, with an average error of 0.1611 meters. In the context of relative positioning within the underground tunnel, the localization error was measured at 0.2143 meters, representing a mere 0.2306% of the total distance covered in the tunnel. These findings affirm the capability of the combined localization method to meet the practical localization requirements of the wheeled-track robot, both in outdoor and in-sheltered space tunnel scenarios.